Transactivation by partial function P53 family mutants is increased by the presence of G-quadruplexes at a promoter site - Vojsovič, Matúš; Kratochvilová, Libuše; Valková, Natália; Šislerová, Lucie; El Rashed, Zeinab; Menichini, Paola; Inga, Alberto; Monti, Paola; Brázda, Václav (Biochimie, 2024)
The effect of mutations in the P53 family of transcription factors on their biological functions, including partial or complete loss of transcriptional activity, has been confirmed several times. At present, P53 family proteins showing partial loss of activity appear to be promising potential candidates for the development of novel therapeutic strategies which could restore their transcriptional activity. In this context, it is important to employ tools to precisely monitor their activity; in relation to this, non-canonical DNA secondary structures in promoters including G-quadruplexes (G4s) were shown to influence the activity of transcription factors. Here, we used a defined yeast assay to evaluate the impact of differently modeled G4 forming sequences on a panel of partial function P53 family mutant proteins. Specifically, a 22-mer G4 prone sequence (derived from the KSHV virus) and five derivatives that progressively mutate characteristic guanine stretches were placed upstream of a minimal promoter, adjacent to a P53 response element in otherwise isogenic yeast luciferase reporter strains. The transactivation ability of cancer-associated P53 (TA-P53α: A161T, R213L, N235S, V272L, R282W, R283C, R337C, R337H, and G360V) or Ectodermal Dyplasia syndromes-related P63 mutant proteins (ΔN-P63α: G134D, G134V and inR155) were tested. Our results show that the presence of G4 forming sequences can increase the transactivation ability of partial function P53 family proteins. These observations are pointing to the importance of DNA structural characteristics for accurate classification of P53 family proteins functionality in the context of the wide variety of TP53 and TP63 germline and somatic mutations.
Keywords: Saccharomyces cerevisiae; Tumor Suppressor Protein p53; G-kvadruplexy; DNA; Mutant Proteins; G-Quadruplexes; Transcription Factors; transkripční faktory; Transcriptional Activation; nádorový supresorový protein p53; mutantní proteiny; aktivace transkripce